1998
DOI: 10.1001/archsurg.133.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Approach and Endoscopic Management of Peripancreatic Necrosis Collections

Abstract: To review the results of the different modalities of treatment of acute necrotizing pancreatitis that have been used by a single team during a 6-year period to assess the technique and indications of an endoscopic method of retroperitoneal drainage that is routinely performed for the management of peripancreatic necrosis.Design and Setting: Retrospective study of 53 patients in a tertiary care center.Results: All patients had signs of peripancreatic necrosis on initial computed tomography scan, 20 patients exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 24 publications
3
84
1
2
Order By: Relevance
“…Indeed, Gambiez et al reported that 2 out of 20 patients developed late hernias through the lumbotomy wound following endoscopic retroperitoneal drainage and both needed reoperation. 16 Minimising the number and length of incisions may therefore prevent this complication, and we have not had any issues with hernias at the laparoscopic port sites.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Gambiez et al reported that 2 out of 20 patients developed late hernias through the lumbotomy wound following endoscopic retroperitoneal drainage and both needed reoperation. 16 Minimising the number and length of incisions may therefore prevent this complication, and we have not had any issues with hernias at the laparoscopic port sites.…”
Section: Discussionmentioning
confidence: 99%
“…Air bubbles can be seen in it on CT examination. In its cavity pseudoaneurysm can develop which can cause fatal bleeding [2,6,11,14,28,33,37]. In those cases where compressive or respiratory complications or pain develop, surgery or less burdensome percutaneous drainage gives an opportunity for treatment, allowing for the descent of the fluid as well as its bacterological examination [3,4,6,8,11,18,24,33,35].…”
Section: Acute Pseudocystmentioning
confidence: 99%
“…The authors do not recommend surgical treatment in the early phase of the illness because of the high morbidity and mortality rates. With the development of interventional radiology and manipulative laparo-endoscopy there are other possibilities to evacuate these fluid collections without operation [1, 6,11,14,21,25,35,40,44]. For the treatment of sterile fluid collection percutaneous puncture and drainage are widely applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Gambiez et al in 1998 have reported their experience of endoscopic retroperitoneal approach in 20 patients via a 6-cm lumbotomy centered on 12 th rib with mean number of 5 lumboscopic procedures required [37].…”
Section: Laparoscopic Surgerymentioning
confidence: 99%